PEMETAAN TATA KELOLA TI DAN ANALISA FAKTOR PENGHAMBATNYA : STUDI KASUS PT BANK DNM, TBK - Alfian Nurdin (University of Muhammadiyah Tangerang, 2018)
Fulfillment of the provision of accurate information and timely in the use, management, effectiveness and responsibility in the banking sector is a must.As a high industry regulation, then needed a good Governance to all sectors including in the field of information technology (it), particularly in the implementation of the principles of Good Corporate Governance.Research using the framework IT Governance as a method of analysis, namely: structure, process, the mechanisms of the relationship; Weill & Ross; ITGI; and AS8015.Then the mapping of the results obtained will be formulated problems facing Banks DNM in it governance.The formulation of the problem is then mapped into a Fishbone Analysis solution is given and try using COBIT 4.1 Best Practice.From the results of this research are expected to Bank DNM can enhance the fulfillment of their needs in terms of information provision to support the implementation of the tasks and functions in the banking sector.